Nota sobre caso autóctone de tripanossomíase americana no litoral sul do Estado de São Paulo, Brasil A case of American Trypanosomiasis in the southern coastal region of S. Paulo State, Brazil - Oswaldo Paulo Forattini; Eduardo Olavo da Rocha e Silva; José Maria Soares Barata; Elias Boainain (Universidade de São Paulo, 1980)
Descreve-se em caso autóctone de tripanossomíase americana no litoral sul do Estado de São Paulo, Brasil. As evidências sugerem a hipótese de a transmissão ter ocorrido graças à contaminação durante o manuseio de carcaças de animais silvestres utilizados na alimentação. An indigenous case of American Trypanosomiasis in the southern coastal region of the State of S. Paulo is reported on. There are no synanthropic triatominae vectors in the area; therefore the transmission mechanism may have been the handling of wild mammal carcasses while they were being prepared for consumption.